The Implementation of Bureaucratic Reform Pillars in Increasing Taxpayer Compliance at Semarang Tax Service Office - Suwandoko, Suwandoko; Rodiyah, Rodiyah (Universitas Negeri Semarang, 2018)
Semarang City Tax Office which has the main task to collect the tax revenue in the context of national development, then the Semarang Tax Office Associate implemented bureaucratic reform pillars in improving tax compliance. This paper examined the compliance of taxpayer in the theory of bureaucratic reform. The paper emphasized that the urgency of the implementation of bureaucratic reform pillars at the Semarang Tax Office, which consists of philosophical, sociological and juridical aspects. The implementation of bureaucratic reform pillars in improving taxpayer compliance at Semarang Tax Office was examined by the implementation model of bureaucratic which influences the bureaucratic reform pillars, which indicates that taxpayer compliance level is less than optimal. The obstacles were employees who are less than optimal in the field of taxation and taxpayers who are less obedient in payment and tax reporting. The efforts did through the socialization of the bureaucratic reform pillars implementation to employees and taxpayers to improve taxpayer compliance and tax revenue.